Long-term effectiveness and outcome predictors of therapist-guided internet-based cognitive–behavioural therapy for social anxiety disorder in routine psychiatric care. Issue 6 (23rd June 2015) - El Alaoui, Samir; Hedman, Erik; Ljótsson, Brjánn; Lindefors, Nils
Abstract : Objectives: Although the short-term outcome of therapist-guided internet-based cognitive–behavioural therapy (ICBT) for treating social anxiety disorder (SAD) has been well studied, little research has been undertaken on the sustainability of treatment gains, especially under clinically representative conditions. Further, there is some debate whether delivering psychological treatment via the internet may be suitable for more severely ill patients. Design: Longitudinal multilevel growth-modelling of long-term (1–4 years) follow-up cohort data. Setting: An outpatient psychiatric clinic specialised in internet interventions. Participants: 446 adults having been treated for SAD. Primary and secondary outcome measures: Primary outcomes were estimated improvement rate and Cohen's d effect size on the self-rated Liebowitz Social Anxiety Disorder Scale. Secondary outcome measures were change in comorbid depressive symptoms and health-related quality of life. Results: A large treatment effect was observed on the primary outcome measure after treatment (d=0.8 (95% CI 0.7 to 0.9)), with continued long-term improvements (d=1.2 (95% CI 1.0 to 1.3)). However, the rate of change varied significantly between individuals over time. A faster rate of improvement was observed among patients with higher illness severity, whereas having a family history of social anxiety was related to worse response. Long-term improvements were also observed in comorbid depressive symptoms (d=0.7 (95% CI 0.5 to 0.8)) and health-related quality of life (d=−0.3 (95% CI −0.4 to −0.1)). Conclusions: These findings provide evidence for the long-term effectiveness of ICBT for SAD in routine clinical practice, even for more severe cases.